(untitled) (Journal of Universal Science Research, 2023)
Enhancing vocabulary proficiency in English is vital for effective communication and academic success. This article provides a concise yet comprehensive overview of proven methods to increase vocabulary in English. The research explores various strategies, including reading extensively, engaging in active listening, utilizing word lists and flashcards, employing mnemonic devices, practicing word association techniques, and utilizing online resources and language-learning apps. The article highlights the importance of context in vocabulary acquisition and emphasizes the role of regular practice and persistence in achieving substantial results. By implementing these effective methods, learners can significantly enhance their vocabulary skills, leading to improved language proficiency and overall communication abilities in English.